PENGARUH KEMANGI DAN KENIKIR SEBAGAI TANAMAN REPELLENT TERHADAP Plutella xylostella Linn. (LEPIDOPTERA:PLUTELLIDAE) PADA BUDIDAYA SAWI ORGANIK - Mulyadi, Hadi; Nasir, Burhanuddin; Yunus, Mohammad (AGROTEKBIS, 2017)
This study aims to determine the effect of basil and marigolds as repellent plants on population density and intensity of attacks of Plutella xylostella and mustard crop production.     The use fulness of this research is for information about the solution in dealing with the attack of    P. xylostella on mustard crop and as pest management of P. xylostella environmentally friendly. The experiment was conducted using a randomized block design method (RBD) consisted of           4 treatments with 3 replications. The treatment consisted of mustard plant is planted in monoculture,  plant basil and marigolds planted together among the mustard plant, basil plants grown with mustard, plant marigolds planted together mustard. Variable observation in this study is the population density, the intensity of P. xylostella, as well as mustrad production. Plant basil and marigolds repellent significant effect on the population density and intensity of P. xylostella and   the production of mustard. Plant basil grown with mustard is the most effective repellent plants treatment compared to other treatments, showed the lowest population density of P. xylostella     (0.1 tail/plant), the lowest attack intensity (1%) and the highest production of mustard 19.52 (tonnes/ha). Key Words: Basil, Marigold, Mustard, Plutella xylostella.